2019
DOI: 10.1016/s2214-109x(18)30478-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Bolsa Familia Programme on the outcome of tuberculosis treatment: a prospective cohort study

Abstract: Background Social protection interventions might improve tuberculosis outcomes and could help to control the epidemic in Brazil. The aim of this study was to evaluate the independent effect of the Bolsa Familia Programme (BFP) on tuberculosis treatment outcomes in Brazil. Methods We prospectively recruited and followed up individuals (aged ≥18 years) who initiated tuberculosis treatment at 42 health-care centres across seven cities in Brazil, between March 1, 2014, and April 30, 2017. Patients were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 20 publications
3
61
1
24
Order By: Relevance
“…These findings corroborate those of previous studies that have found positive associations of government direct income transfer programs with success/cure following treatment. 14,15,16 The association between social protection strategies and successful treatment and cure of individuals with TB was also observed in a meta-analysis of studies carried out in Brazil and in other countries with similar levels of income and disease burden. 11 Among the limitations of our study, we include (i) the absence of data on the length of time and/or discontinuity of benefit receipt during treatment, given that such information was obtained at the time of diagnosis, (ii) the absence of measurement of the frequency of receipt of each benefit and the number of beneficiaries in each family affected by the disease and (iii) the possibility of non-response bias, since some participants were reluctant to report receipt of benefits for fear of losing them.…”
Section: Tuberculosis Treatment Outcome and Social Benefits In Salvadmentioning
confidence: 69%
See 2 more Smart Citations
“…These findings corroborate those of previous studies that have found positive associations of government direct income transfer programs with success/cure following treatment. 14,15,16 The association between social protection strategies and successful treatment and cure of individuals with TB was also observed in a meta-analysis of studies carried out in Brazil and in other countries with similar levels of income and disease burden. 11 Among the limitations of our study, we include (i) the absence of data on the length of time and/or discontinuity of benefit receipt during treatment, given that such information was obtained at the time of diagnosis, (ii) the absence of measurement of the frequency of receipt of each benefit and the number of beneficiaries in each family affected by the disease and (iii) the possibility of non-response bias, since some participants were reluctant to report receipt of benefits for fear of losing them.…”
Section: Tuberculosis Treatment Outcome and Social Benefits In Salvadmentioning
confidence: 69%
“…2,10 Despite scarce knowledge on access and coverage of social programs and benefits for people with TB, recent evidence has pointed to their direct 15 or indirect positive effects on the improvement of treatment outcomes of these individuals, especially the poorest ones. As these findings relate only to the Bolsa Família program, [13][14][15][16] new studies are needed to investigate the effects of other social protection benefits on TB indicators. The Bolsa Família program is the most relevant social program in Brazil and one of the largest in the world.…”
Section: Education Level (In Years Of Schooling )mentioning
confidence: 99%
See 1 more Smart Citation
“…Areas with high BFP coverage have been shown to correlate with lower incidence of tuberculosis, but the association between the BFP programme and tuberculosis treatment outcomes is less clear. 8 The authors analysed the treatment outcomes of 1239 individuals treated for tuberculosis, of whom 196 (16%) patients qualified for and received BFP and 1043 (84%) patients did not. The findings suggest that although the proportion of patients who were cured of tuberculosis in the BFP group was not significantly different from that of patients in the non-BFP group (173 [88%] of 196 patients vs 912 [87%] of 1043 patients, p=0•774), propensity score matching showed that rate of cure was 7•6% higher and the proportion of patients who dropped out was 7% lower in the BFP group than the non-BFP group and these differences were statistically significant.…”
Section: Social Protection Interventions Could Improve Tuberculosis Tmentioning
confidence: 99%
“…www.thelancet.com/lancetgh Vol 7 February 2019 score matching analysis was used to overcome this limitation by estimating the conditional probability of an individual being beneficiary on the basis of their observed characteristics. 8 However, as a result of the relatively small sample size of the BFP beneficiaries used for propensity score matching, the possibility of residual confounding from covariates that are mostly missing or remain unbalanced cannot be ruled out.…”
Section: Comment E168mentioning
confidence: 99%